2022
DOI: 10.1002/rth2.12669
|View full text |Cite
|
Sign up to set email alerts
|

MUlticenter STudy of tissue plasminogen activator (alteplase) use in COVID‐19 severe respiratory failure (MUST COVID): A retrospective cohort study

Abstract: Background Few therapies exist to treat severe COVID‐19 respiratory failure once it develops. Given known diffuse pulmonary microthrombi on autopsy studies of COVID‐19 patients, we hypothesized that tissue plasminogen activator (tPA) may improve pulmonary function in COVID‐19 respiratory failure. Methods A multicenter, retrospective, observational study of patients with confirmed COVID‐19 and severe respiratory failure who received systemic tPA (alteplase) was performed. Seventy‐nine adults from seven medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In most cases, systemic fibrinolysis with alteplase proved effective. Other authors also reported clinical improvement in critically ill patients with COVID-19 after fibrinolytic therapy [ 14 , 44 , 45 , 46 ]. It is suspected that pulmonary microemboli may contribute to respiratory failure in patients with COVID-19.…”
Section: Fibrinolysis In Critically Ill Patients With Covid-19: Yes O...mentioning
confidence: 98%
“…In most cases, systemic fibrinolysis with alteplase proved effective. Other authors also reported clinical improvement in critically ill patients with COVID-19 after fibrinolytic therapy [ 14 , 44 , 45 , 46 ]. It is suspected that pulmonary microemboli may contribute to respiratory failure in patients with COVID-19.…”
Section: Fibrinolysis In Critically Ill Patients With Covid-19: Yes O...mentioning
confidence: 98%
“…In patients with severe COVID-19, the use of fibrinolytic therapy with tissue plasminogen activator may improve pulmonary outcomes. In a retrospective study with 79 patients, the use of alteplase was associated with improvements in oxygenation parameters [ 47 ]. Alteplase showed to be safe in a phase 1–2 study with 50 randomized patients.…”
Section: Other Antithrombotic Treatmentsmentioning
confidence: 99%
“…[ 8 ] No guidelines are currently available to directly address the use of tPA to treat PE in COVID-19 patients; however, various studies have been performed. [ 9 10 11 ]…”
mentioning
confidence: 99%